A history of undescended testes in young men with Klinefelter syndrome does not reduce the chances for successful microsurgical testicular sperm extraction. (21st June 2018) - Ragab, M. W.; Cremers, J.‐F.; Zitzmann, M.; Nieschlag, E.; Kliesch, S.; Rohayem, J.
Summary: Klinefelter syndrome (KS) and undescended testes (UDT) are known etiologies for non‐obstructive azoospermia (NOA), and coexistence of both etiologies is not uncommon. Patients with both KS and a history of UDT are therefore considered to have extremely reduced chances for paternity. We aimed to analyze the impact of previous surgically corrected unilateral or bilateral UDT on sperm retrieval rates (SRRs) by microsurgical testicular sperm extraction (mTESE) in azoospermic men with KS. Age, testicular volumes, and hypothalamo–pituitary–gonadal axis function were investigated in relation to SRRs in 29 non‐mosaic KS patients (47, XXY) with a history of UDT (group 1) who underwent mTESE between 2008 and 2016 in our center and compared to the data of age‐ and serum testosterone‐matched non‐mosaic KS controls with eutopic testes at birth (group 2), and to those of 51 men with NOA and a normal male karyotype (46, XY), but previous UDT (group 3). SRRs in KS patients with surgically corrected UDT during childhood were comparable to SRRs of KS patients with eutopic testes at birth: 31% (35% in unilateral and 22% in bilateral UDT) vs. 38% ( p = 0.581). SRRs and Leydig cell function in group 1 were negatively correlated with age. Significantly higher SRRs (66%) were found in euploid azoospermic men with surgically corrected UDT ( p < 0.001). A history of UDT does not preclude chances for future fatherhood in young azoospermic males with KS. In one of three men with previous unilateral UDT and in one of 4–5 in those with previous bilateral UDT, spermatozoa can be harvested by mTESE during late adolescence or young adulthood for immediate or future use in assisted reproduction.